STUDENT PERCEPTION IN LEARNING ENGLISH SPEAKING ABILITY THROUGH IMPLEMENTING INSTAGRAM - Salma Aldarosa Anjani; I Gusti Ayu Lokita Purnamika Utami; Ni Luh Putu Sri Adnyani (PROJECT (Professional Journal of English Education), 2024)
This study research is aimed to examine the perceptions of students regarding the use of Instagram for improving English speaking skills. Social media platforms, including Instagram, have gained popularity in language learning contexts, yet little research has examined students' perspectives on its efficacy. The type of this research used quantitative research design. The quantitative with survey study technique. A population of forty-eight students participated, representing hospitality educational backgrounds and proficiency levels at Apollonia Hotel School in the academic year 2022/2024 in diploma II. The instrument for collecting data was a questionnaire. Semi-structured questionnaires assess participants' usage patterns, perceived benefits, challenges, and attitudes toward Instagram for language learning. The data analysis used validity, reliability of Cronbach Alpha, and descriptive statistics by using SPSS version 26. The result indicated a generally positive perception of Instagram as a supplementary tool for English-speaking practice, highlighting benefits such as access to authentic language content and interaction opportunities with native speakers. However, distractions were also noted from an unstable internet connection, the informal nature of the content, and the experience of the teacher to transform in teaching environment from traditional to innovative ways. Further research is recommended to explore effective strategies for integrating Instagram into language learning curricula and addressing the identified challenges.